The family Hydroptilidae Curtis (Trichoptera) in the Ogasawara Islands, northwestern Pacific, with particular reference to adaptive radiation in the oceanic islands - Ito, Tomiko; Sasaki, Tetsuro; Takahashi, Chicaco; Sugawara, Hirotaka; Hayashi, Fumio (Zootaxa, 2023)
The caddisfly family Hydroptilidae Curtis was revised for the oceanic Ogasawara (Bonin) Islands, northwestern Pacific. Six endemic species of the genus Hydroptila Dalman 1819 (H. demersa Ito & Sasaki sp. nov., H. ishiura Ito & Sasaki sp. nov., H. tokoyo Ito & Sasaki sp. nov., H. hahajima Ito & Sasaki sp. nov., H. nagahama Ito & Sasaki sp. nov. and H. ogasawaraensis Ito 2011, in Ito et al. 2011) are recognized based on larval and adult morphology and molecular analysis. Each of six species was not distributed widely but limited to a narrow area: H. ogasawaraensis on Chichi-jima, H. tokoyo on southern Chichi-jima, H. demersa and H. ishiura on Ani-jima and northern Chichi-jima, H. hahajima on southern Haha-jima, and H. nagahama on central Haha-jima. This speciation pattern in the small area might be an example of adaptive radiation in these oceanic islands. The larva of H. demersa has an elongate and depressed head capsule and makes a slightly compressed case with rough surface, suggesting that it inhabits the hyporheic zone, where aquatic organisms are scarce in the oceanic islands. The other five species, H. ishiura, H. tokoyo, H. hahajima, H. nagahama, and H. ogasawaraensis, were often found in hygropetric habitats and small waterfalls, where other species of microcaddisflies are absent. Small dorsal sclerites of abdominal segments I–III of larvae in the five species may be another adaptation to this microhabitat with rapid water flow.